2021
DOI: 10.1186/s12904-021-00729-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic adaptation of the Thai version of the supportive and palliative care indicators tool for low-income setting (SPICT-LIS)

Abstract: Background Identification of patients who might benefit from palliative care among countries with different socioeconomic and medical contexts is challenging. The Supportive and Palliative Care Indicators Tool for a Low-income Setting (SPICT-LIS) was designed to help physicians identify patients in low-income setting who might benefit from palliative care. We aimed to systematically adapt and refine the SPICT-LIS for Thai general palliative care providers. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Our study found that SPICT-CH has an acceptable agreement between inter-rater reliability nurses, demonstrating a good stability of instrument. The inter-rater consistency (Kappa = 0.71) of SPICT-CH is higher than that (Kappa = 0.66) of the Thai version of SPICT [21]. It possibly due to the different composition of assessors in the studies.…”
Section: Discussionmentioning
confidence: 78%
“…Our study found that SPICT-CH has an acceptable agreement between inter-rater reliability nurses, demonstrating a good stability of instrument. The inter-rater consistency (Kappa = 0.71) of SPICT-CH is higher than that (Kappa = 0.66) of the Thai version of SPICT [21]. It possibly due to the different composition of assessors in the studies.…”
Section: Discussionmentioning
confidence: 78%
“…Ten of the included studies were conducted in primary care and general practice settings 20 22 24 25 30 32 37 38 . The SPICT™ was also used in outpatient clinic settings 23 28 39 and residential aged care 29 35 .…”
Section: Resultsmentioning
confidence: 99%
“…There were multiple study designs including validation and translation (n = 6) studies [17][18][19][20][21][22] and clinical improvement projects (n = 3) [23][24][25] . The focus of the clinical improvement projects was to increase the identi cation of palliative care needs and care planning through the use of the SPICT™.…”
Section: Resultsmentioning
confidence: 99%